64 Magnetic resonance of the small bowel with early (70s) and late (7MINS) phase post gadolinium imaging to identify fibrosis in stricturing small bowel crohn's disease. (5th April 2017) - Stack, R; O'Brien, C; Nuzum, T; Cummins, S; Hussey, M; O'Morain, N; O'Connor, A; Breslin, N; Ryan, B; Murphy, I; McNamara, D
Abstract : Background: Strictures are a serious complication of Ileal Crohn's disease (CD). Current assessment tools poorly differentiate fibrotic from inflammatory lesions and do not predict response. The magnetic resonance index of activity (MaRIA) is a validated means to assess activity. Its ability to characterise fibrosis remains unclear. Recent evidence suggests relative contrast enhancement (REC) of >24% on delayed MRI sequences may accurately detect fibrosis. Aim: Compare MaRIA, RCE and biochemical activity in patients with Ileal CD. Method: Prospective study of patients undergoing MRE for known CD. MRE was performed as standard with additional coronal T1 sequences 7 min post gadolinium administration. Two independent blinded Radiologists calculated RCE and MaRIA's at 70 s and 7 min. Demographics and CRP were recorded. Results: 26/29 MRE's performed had ileal CD, median age=41 years, male=10 (38%). RCE >24% and high T2 signal intensity (SI); 6/26 (23%) and 11/26 (42.3%). REC >24% occurred in only 1/10 with a visible stenosis. Average MaRIA's: 2/26 (7.7%)<7 mild; 3/26 (11.5%) 7-11 moderate; 21/26 (80.7%)>11 severe. MaRIA's did not change significantly between 70 s and 7 min. As expected T2 SI increased with MaRIA's>11, 26 v 13 (p<0.001, 95% CI 7.73 to 17.27). RCE did not correlate with MaRIA group, ? 0.09. Consistent with MRE findings, CRP was higher in patients with MaRAI >11 (13.3 vs 5.2) and lower in patients with RCE >24% (3.9 vs 14), p<0.04 95% CI 0.37 to 15.71 and p<0.01 95% CI 2.5 to 19.05 respectively. Conclusions: RCE may be a useful adjunct to current MRE and help detect fibrosis in small bowel lesions and warrants further investigation.